Demonstration of a negative reinforcement preference assessment to determine aversiveness of types of social interaction. (20th November 2021) - Slocum, Sarah K.; Scheithauer, Mindy; Muething, Colin
Abstract: Prior researchers have validated the use of a latency assessment to create a hierarchy of demand aversiveness. Demand latency assessments help to identify high‐aversive demands for use in functional analyses and/or treatment. The current study used the same approach to evaluate aversiveness of social interaction among four individuals who engaged in target behavior maintained by social avoidance. We obtained clear hierarchies in social interaction aversiveness across all participants. For one participant, we also used the social avoidance latency assessment to demonstrate an intervention approach using gradual fading of less‐ to more‐aversive forms of social interactions. These results indicate latency assessments may be applicable to generate hierarchies of aversive situations that may evoke target behavior maintained by social negative reinforcement other than escape from demands, leading to several clinical implications, and future research directions.